2011
DOI: 10.1143/jpsj.80.013602
|View full text |Cite
|
Sign up to set email alerts
|

Surface Majorana Cone of the Superfluid 3He B Phase

Abstract: The superfluid3 He B phase, one of the oldest unconventional fermionic condensates experimentally realized, is recently predicted to support Majorana fermion surface states. Majorana fermion, which is characterized by the equivalence of particle and antiparticle, has a linear dispersion relation referred to as the Majorana cone. We measured the transverse acoustic impedance Z of the superfluid 3 He B phase changing its boundary condition and found a growth of peak in Z on a higher specularity wall. Our theoret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
101
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 26 publications
(97 reference statements)
2
101
0
Order By: Relevance
“…The angular momenta L MJ and L cont can be suppressed by the different rates as a function of the surface roughness. Here we notice in the case of the superfluid 3 He B-phase that the surface Majorana bound state remains at a partially specular surface [9,10]. The concrete calculation to estimate quantitatively this change is a future problem.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The angular momenta L MJ and L cont can be suppressed by the different rates as a function of the surface roughness. Here we notice in the case of the superfluid 3 He B-phase that the surface Majorana bound state remains at a partially specular surface [9,10]. The concrete calculation to estimate quantitatively this change is a future problem.…”
mentioning
confidence: 77%
“…The Majorana nature for the A-and B-phases is also distinctive; Majorana Fermions have the surface Andreev bound state with linear dispersion relation centered at the zero energy forming a "Majorana valley" in the A-phase [4,5] and a "Majorana cone" in the B-phase [6][7][8]. This Majorana cone is emerging by recent experiments [9,10]. However, there has been no firm evidence for detecting the Majorana zero mode.…”
mentioning
confidence: 99%
“…At the weak coupling limit, the planar is energetically degenerate to the A-phase that is the time-reversal symmetry breaking phase with point nodes, while the strong coupling effect that is the spin-fluctuation feedback effect can stabilize the A-phase relative to the planar phase and the A-B phase boundary becomes the first order transition. The pair breaking effect and the enhancement of the surface density of states due to the surface bound state have been observed by several experiments, by using the NMR techniques [112,113,114,115,116,117,118,155,156,157], the motion of a vibrating wire resonator [158], transverse acoustic impedance [162,163,164,165,166,167,168,169], surface contributions of the heat capacity [160], and anomalous attenuation of transverse sound [161]. Among them, Murakawa et al [165,168] has observed the specularity dependence of the surface density of states by systematically controlling the surface specularity by coating the surface with 4 He layers.…”
Section: Thermodynamics In the Absence Of Dipole-dipole Interactionmentioning
confidence: 99%
“…The surface density of states has a very sharp edge at E = ∆ * that is smaller than the bulk energy gap ∆ 0 . The temperature dependence of the complex impedance observed two different energy scales ∆ * and ∆ 0 [162,163,164,165,166,167,168,169] as a kink and peak in Z ′ (T ) and Z ′′ (T ). The remarkable point is that the surface specularity is controllable by coating the wall of the transducer with thin layers of 4 He.…”
Section: Transverse Acousticsmentioning
confidence: 99%
“…On the surface of 3 He B phase, a clear linear dispersion of in-gap states was measured experimentally 18 . In addition, the newly found superconducting phase in Cudoped Bi 2 Se 3 19 has been proposed to be a 3d-TSC 20 .…”
mentioning
confidence: 98%